Pengembangan Aplikasi Virtual Tour sebagai Media Pengenalan Lingkungan Kampus PENS berbasis Website - Fauzan, Ashafidz; Maisat Eka, Zakha; Fairozal Akbar, Zulhaydar; Fathoni, Kholid (LPPM STT Terpadu Nurul Fikri, 2021)
The introduction of the New Student Campus Life (PKKMB) activity at The Electronics Engineering Polytechnic of Surabaya (EEPIS) is limited in its implementation due to the never-ending Covid-19 pandemic. All activities involving large numbers of people must carry out online to avoid the spread of the Covid-19 virus. With this policy, an application that can describe the campus life environment online is needed, so digital virtual reality media makes, namely Virtual Tour. The user interfaces in this application design using the Balsamiq application so that the resulting display is more attractive and interactive. A virtual tour application created using multi panoramic images, where 360Âº panoramic images taken using a 360 camera taken at several campus locationsâ€”making a virtual tour application using the 3DVista application. The application development method used in this research is Multimedia Development Life Cycle (MDLC). From the test results of the website-based virtual tour application created, this application can display the environment and facilities owned by the EEPIS campus and can run according to its functionality, and can use by students to recognize the campus environment.